Exploring the effect of Er miao San-containing serum on macrophage polarization through miR-33/NLRP3 pathway. (10th May 2023) - Liu, Min; Wang, Jin; Chen, Simeng; Meng, Xiangwen; Cheng, Zhiluo; Wang, Jiayu; Tan, Yanan; Su, Wenrui; Lu, Zhiyuan; Zhang, Min; Jia, Xiaoyi
Abstract: Headings ethnopharmacological relevance: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease. Er miao San (EMS) has been shown to have good anti-inflammatory effects and is widely used in the clinical treatment of RA. However, the exact mechanism is not completely understood. Aim of the study: The aim of this study was to explore that EMS-containing serum affects M1/M2 polarization of macrophages and may be mediated through the microRNA (miRNA)-33/NLRP3 pathway, thereby elucidating the molecular mechanism of EMS treatment of RA. Materials and methods: We screened for safe concentrations of EMS-containing serum by using CCK-8 measurement. RAW264.7 cells were cultured with lipopolysaccharide (LPS) (100 ng/mL) and interferon-γ (20 ng/mL) for 24 h to induce M1-type macrophages. Adenosine triphosphate (ATP) (5 mM) was added in the last 30 min to activate NLRP3. The content of miR-33 was detected by RT‒qPCR after transfection of the miRNA-33 mimic. The protein expression levels of NLRP3, ASC, caspase-1, Inducible Nitric Oxide Synthase (iNOS) and Arginase-1 (Arg-1) were detected by Western blot. The contents of IL-1β, IL-10, TNF-α, TGF-β and IL-18 in serum and cell supernatant were determined by ELISA. The fluorescence intensity of CD86 and CD206 was detected by immunofluorescence. Results: The results showed that EMS-containing serum promoted the protein expression level of Arg-1 and the secretion levels of TGF-β and IL-10, inhibited the levels of iNOS, IL-1β and TNF-α, and regulated the balance of pro-inflammatory factors and anti-inflammatory factors. RT‒qPCR results showed that EMS-containing serum could reduce the level of miRNA-33. EMS-containing serum could reduce the expression of NLRP3 inflammasome-related proteins and downregulate the expression levels of IL-1β and IL-18. These results suggest that EMS exerts its effect on macrophage polarization through the miRNA-33/NLRP3 pathway. Conclusion: EMS-containing serum inhibits the activation of the NLRP3 inflammasome by downregulating miRNA-33, thus preventing the polarization of M1-type macrophages. Graphical abstract: Image 1